Pelatihan Mendesain Media Pembelajaran Trainer Sensor dan Transduser - Purnamawati Purnamawati; Muhammad Akil; Nuridayanti Nuridayanti (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
Abstract. This PKM partner is SMK Negeri 2 Makassar. The main problem of this activity is the lack of instructional media and teacher motivation in preparing the learning media. As a result, the learning process runs as it is, students only note, learning devices are not designed systematically with incomplete facilities and infrastructure. Therefore, training was conducted for productive teachers majoring in electronic engineering at SMK Negeri 2 Makassar in order to develop their competence in the field of making learning media in the form of trainers. This activity is carried out by means of lectures, discussions, questions and answers, and companion partners. The results achieved in this activity were obtained by sensor and transducers trainer as practical learning media for students. In addition, indicators of the success of implementing the design of the sensor and transducer trainer instructional media show satisfactory results as seen from the results of evaluation and monitoring of the trial use of sensor and transducer trainers by teachers at SMK Negeri 2 Makassar. The results of the trial using trainers showed that 94% of the teachers were able to simulate a series before practicing directly on the trainer, 82% of the participants were able to program and 76% of the participants were able to assemble and use the sensor and transducer trainers. As well as the teacher's response to this Community Service activity, it shows that 88% of participants expressed satisfaction with this activity.